KEAKURATAN HASIL TERJEMAHAN MAHASISWA POLITEKNIK NEGERI BALI - I Nyoman Rajin Aryana (Program Magister Linguistik Universitas Udayana, 2013)
A translation is considered to be good when it can transfer meaning and information of Source Language (SL) to Target Language (TL) accurately, clearly and naturally. The aim of this study is to identify and know the accuracy of the translation works done by Students of Tourism Department of Bali State Polytechnic. An accurate translation may produce clear and natural meaning as it is usually used in the Target Language (TL). The data source in this study was taken from the translation works done by The Tourism Department Students of Bali State Polytechnic where they were asked to translate a text about tour program. The source language of the text is Indonesian while the target language which is English. The findings showed that the accuracy of the students translation works done by Students of Tourism Department of Bali State Polytechnic still needs greatly to be improved. There were many basic English Grammar mistakes made by the students as well as wrong diction or choice of words to transfer meaning from SL to TL. This situation caused the transfer of meaning and information from the source language to the target language could not be done well and made the translation considered to be not good.